Radon Gas Detection of Soil Samples in Primary Schools at Najaf City, Iraq - Dosh, Rukia J.; Hasan, Ali K.; Abojassim, Ali A. (Jordan Journal of Physics, 2024)
Abstract: The radon concentration, specific activity of 226Ra (CRa), and 238U concentrations (CU) in soil samples from 100 primary schools of Al-Najaf province, Iraq, were measured to determine the safety of students and staff using the CR-39 nuclear track detector based on the sealed can technique. The mean values of 222Rn concentration in the air space of the container (C) and the soil sample (CRn) were 23.53±1.149Bq/m3 and 960.38±47 Bq/m3, respectively. The mean values of CRa and CU were 0.035±0.002 Bq/kg and 0.043±0.002 ppm, respectively. The 222Rn,226Ra, and 238U concentrations were lower than the worldwide level. Radiological parameters such as annual effective dose (AED) and radon exhalation rate per unit mass (EM) and per unit surface (ES) also were determined. The results indicate normal levels for these parameters, except for higher values of AED in some primary schools, according to UNSCEAR data.